Founder Narcissism and IPO Performance - Uzakova, Aizhan (2024)
A Master of Science thesis in Finance by Aizhan Uzakova entitled, “Founder Narcissism and IPO Performance”, submitted in May 2024. Thesis advisor is Dr. Kimberly C. Gleason and thesis co-advisor is Dr. Iness Aguir. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).